Anti-γ-aminobutyric acid-A receptor encephalitis with refractory seizures and cognitive impairment in a young woman: A case report - Yang, Xue; Deng, Bo; Wang, Shengjun; Wang, Xiaotang; Cao, Lili; Chen, Xiangjun; Zhao, Xiuhe (Frontiers in Neurology, 2022)
Anti-γ-aminobutyric acid-A receptor (GABAAR) encephalitis is an underappreciated cause of autoimmune encephalitis and remains refractory to antiepileptic therapies unless autoimmune responses are addressed. Herein, we reported a case of anti-GABAAR encephalitis in a young woman. A 29-year-old woman was admitted because of seizures for 10 months, memory decline for 7 months, and paroxysmal limbs jerking for 5 months. At admission, the patient showed mild cognitive impairment. Cell-based assays found no antibodies associated with common autoimmune encephalitis in the cerebrospinal fluid (CSF) and no antibodies in the plasma and CSF against central nervous system demyelination-associated proteins. MRI revealed multiple cortical-subcortical abnormalities and electroencephalography demonstrated periodic epileptiform discharges during paroxysmal clonus. A second test 1 month after admission detected antibodies against GABAAR α1/β3/γ2 in the plasma and CSF, leading to a diagnosis of anti-GABAAR encephalitis. The patient received intravenous immunoglobulin, prednisone, azathioprine, and levetiracetam and recovered from limb jerks and was no longer amnesic. A second episode occurred after an apparent cold and was managed by intravenous immunoglobulin, cyclophosphamide, and methylprednisolone with subsequent prednisone and levetiracetam. The patient was able to speak and ambulate after 15 days of treatment. Her MMSE, MoCA, and MRS scores improved. Physicians should harbor a high index of suspicion of anti-GABAAR encephalitis in refractory encephalitis patients with the manifestation of seizures or psychiatric disorders. Tests for a comprehensive panel of antibodies associated with anti-GABAAR encephalitis should be carried out in suspected cases and immunotherapy should be promptly initiated upon diagnosis to prevent irreversible neurological damage.